Innovative Strategy of KBIHU, Mayor of Semarang Regency in Hajj Guidance to Improve the Quality of Services for Group 35 Pilgrims - Mohammad Riefqy Adhlitama (Penerbit Hellow Pustaka, 2025)
This research explores the innovative strategies implemented by Kelompok Bimbingan Ibadah Haji dan Umrah (KBIHU) Wali, Semarang Regency, in improving the quality of hajj guidance for group 35 pilgrims. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation. The findings reveal that KBIHU Wali applies a comprehensive concept called Haji Mandiri (Independent Pilgrimage), which emphasizes continuous manasik training, simulation-based learning, spiritual strengthening, and the use of digital media in the mentoring process. These strategies have increased pilgrims’ independence, readiness, and satisfaction with the services provided. This study contributes to the understanding of innovative hajj guidance models and offers insights for other KBIHUs to enhance their service quality.